Cost optimization based on joint economic lot size model by incorporating transportation costs for single sullpier-purchaser - Raden Achmad, Chairdina Leuveano (2014)
The increasing focus on supplier-purchaser coordination has become an essential issue to be managed efficiently in optimizing supply chain's performance. Procurement scenario indicates that most of supplier and purchaser have emphasized their effort in effective decision for inventory replenishment independently. Instead of independent decision, Joint Economic Lot Size (JELS) model has been proposed as the representation of coordinated decision between supplier-purchaser. The main objective is to minimize joint total cost of supplier and purchaser by jointly deciding the optimal order quantity, batch production lot, and number of deliveries. Determination of inventory replenishment need to consider transportation as the function of shipment weight and haulage distance that simultaneously emulate freight rate schedules and two modes of transportation namely Truckload (TL) and Less than Truckload (LTL) shipment. Hence, this study proposes to incorporate transportation or freight cost function into JELS model. There are three proposed models in this study, namely: (i) JELS-Inverse (JELS-I) for emulating TL shipment, (ii) JELS Adjusted-inverse (JELS-A) for emulating LTL shipment, and (iii) JELS Lot-splitting (JELS-L) for minimizing joint total cost if the transportation is limited based on TL and LTL shipment. JELS-I and JELS-A constitutes the analytical mathematical model that validated using sensitivity analysis to analyze the robustness of the model. JELS-L is a model based Heuristic optimization approach to search solution within the interval solution of JELS-I and JELS-A. The models are examined by the numerical example for analyzing its feasibility in deriving the solution. The result shows that JELS-I provides a large order quantity but a small number of deliveries, otherwise, JELS-A yields smaller order quantity but a higher number of deliveries. Both models only resulting minimum joint total cost in the case of TL and LTL shipment meanwhile JELS-L performs better result than other models in minimizing joint cost. The models tested by experimenting the wide range of model parameter in order to analyze the effectiveness of the model in yielding a best solution to minimize joint total cost. The experimental result shows that JELS-L provides a smaller deviation toward the best solution rather than another model. It can be indicated that JELS-L model successfully gives promising results in a coordinated decision of the supply chain.